Imaging post liver transplantation part I: vascular complications. Issue 11 (November 2020) - Zhong, J.; Smith, C.; Walker, P.; Sheridan, M.; Guthrie, A.; Albazaz, R.
Abstract : Liver transplantation continues to rise in frequency, with over 1, 000 procedures performed in the UK in 2018. Complications are increasingly uncommon but when they occur, early recognition and intervention is vital to save grafts. Imaging after the perioperative period is often performed at patients' local hospitals meaning that all radiologists and sonographers need to have an understanding of how to assess a transplant liver. Part I of this series will focus on vascular complications, including the normal postoperative vascular anatomy following liver transplantation, normal post-transplantation vascular imaging findings and abnormal findings that may prompt further investigation. Vascular complications following liver transplantation will be illustrated using a collection of cases.